Metadata and the Archival Management of Electronic Records: A Review - Wallace, David A. (Archivaria, 1993)
Several of the most influential and prolific electronic records archivists have advocated a metadata systems approach to the management of electronic records. This essay introduces the metadata concept and reviews both its context and its content in the "second generation" of electronic records archives and scholarship. These writings theorize that a metadata systems approach will affect archival appraisal and preservation, and fundamentally alter arrangement, description, and reference. A survey of four leading electronic records programmes examines their metadata applications and underscores the value of this approach for other archivists. It is concluded that a metadata systems approach will become the basic strategy for archivists seeking to manage electronic records systems. To be successful, this strategy will require archivists to become proactive, develop new technological skills, and commit themselves to multidisciplinary collaborations. RÉSUMÉ Plusieurs des plus prolifiques et importants archivistes spécialisés dans le domaine des documents informatiques ont plaidé pour une approche méta-informationnelle de la gestion des dossiers électroniques. Cet essai présente le concept de méta-information et examine à la fois son contexte et son contenu dans la «deuxième génération» des études relatives aux documents électroniques. Ces écrits émettent l'hypothèse qu'une approche des systèmes méta-informationnels aura des conséquences sur l'évaluation archivistique, la conservation, le classement, la description et la référence. Le survol de quatre importants programmes de données électroniques met en relief leurs applications méta-informationnelles et met en évidence le bien-fondé de cette approche pour d'autres archivistes. Une approche des systèmes méta-informationnels va devenir la stratégie fondamentale des archivistes chargés de la gestion des systèmes des documents informatiques. Pour être fructueuse, cette stratégie va requérir le dynamisme des archivistes, qu'ils développent de nouvelles aptitudes technologiques et s'engagent dans la multidisciplinarité.